Development of Method and Validation for Related Substances in Docetaxel Injection Formulation with HPLC - Korupolu Nagu, B. Vinu, B. S. A. Andrews, V. D. N. Kumar Abbaraju, Kancharla Vijayalakshmi, G. T. Jyotesh Kumar (Forest Chemicals Review, 2022)
A validated HPLC method is developed to determine Docetaxel (DTX) in pharmaceutical formulation. Isocratic elution at a flow rate of 1.00ml/min is employed on Zorbax XDB C18 150mm × 4.6 mm, 5µ Column, or equivalent. Exactly transferred 1100 volumes of water and 900 volumes of Acetonitrile as a mobile phase. U.V. detection wavelength is set at 230nm. An injected sample is 10.0μl.   Run time is 22 minutes for Sample, Blank, Placebo, and regular. The approximate retention time identified to DTX is 6.0 min. % R.S.D DTX is identified. Mean Percentage recovery to DTX is identified within the specification limit. This work is validated by using rules and regulations given by ICH. Therefore, the proposed HPLC process should successfully be applied to routine quality control analysis formulations. This process developed is simple and better than that of different processes reported in earlier literature. Values permit application for proposed stability-indicating HPLC methodology in syrup dose forms.